THE VALIDITY OF STUDENT WORKSHEET BASED MODEL INQUIRY TO INCREASE PROCESS SKILLS ON THE TOPIC METABOLISM FOR GRADE XII SENIOR HIGH SCHOOL - Mulyaningsih, Sunda; Yuliani, Yuliani; Yakub, Pramita (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2018)
Learning inquiry model is one that promotes learning model to be able to find problem and can solve the problem independently. Phase inquiry model there are six stages: the orientation phase, the phase of formulating the problem, proposed a hypothesis phase, the phase of collecting data, hypothesis testing phase, and the phase of formulating its conclusions. The validity of student worksheet based on the 3 specialist validation. There were two student worksheet developed, that are student worksheet 1 discussing the topic of katabolism and student worksheet 2 discussing the topic of anabolism. The research was 4-D models that are define, design, develop and disseminate stage was not implemented. Data analysis of the validation result was done theoretically and empirically. Validation results indicate that the developed of student worksheet was categorized very valid with the persentage reaches 3.65 for student worksheets 1 and 3.68 for student worksheet 2. Skill of process outcomes showed that students experience increased science of N-gain obtained 0.70 which was categorized as high. The percentage of total students who reached minimal completeness of criteria (complete) at the posttest obtained 95% with minimal completeness of criteria 75 and the completeness of indicators obtained 81,5% complete of 7 indicators at the posttest.Keywords: The Student’s Worksheet (LKPD), Inquiry Model, Process Skills, Metabolism